Characterizing ASOCOPI: Its Affiliates, Ideals, and Contributions - Edgar Lucero; Zulay Díaz (Asociación Colombiana de Profesores de Ingles, 2016)
This article presents the results of an on-line cross-sectional questionnaire and further discussion about the characterization of ASOCOPI's affiliates, their expectations of being a member, and the contributions that the association has made to their professional development. The respondents' answers were analyzed by following a statistical analysis and a content analysis under a survey research approach. Findings reveal that the Association has highly qualified and experienced English teachers who maintain expectations in relation to encountering opportunities to update its teaching and research knowledge, creating professional links, and knowing about academic events and studies in the field. Contributions are oriented to their teaching, research, and professional practices. Discussion highlights prominent issues about the Association's profile, trends, and ideals.